Analisis Proses Konsolidasi Dengan PVD Pada Proyek Reklamasi di Samping Tangki CPO Antar Pulau Belawan Berdasarkan Bore Log BH-1 - Amirah Hanun; Roesyanto; Gina Cynthia R. Hasibuan (Jurnal Syntax Admiration, 2023)
In the planning of civil building, construction problems are often encountered in soft soil types, including low soil carrying capacity and large settlements (settlements) when given a load. Soil improvement is needed to speed up the consolidation settlement time. One method that can be applied to speed up the consolidation settlement time is to use a pre-fabricated vertical drain (PVD) and this preloading method is able to increase the shear strength of soft soils and remove pore water in the soil. This research aims to determine the magnitude of settlement of soft soil consolidation using the 1-dimensional Terzaghi consolidation formula and analysis using the finite element method with PLAXIS 2D modeling, comparing the results of PLAXIS 2D modeling with actual data, the effect of the smear zone effect on the settlement of soil consolidation in the embankment area and to determine the difference in the decrease in preloading methods combined with PVD and preloading without PVD based on point bore log BH-1. From the results of the analysis, it is found that the consolidation settlement by analytical method using the 1-dimensional Terzaghi consolidation formula was 0.858 meters. The amount of settlement that occurs in the consolidation process using PLAXIS 2D modeling taking into account the smear zone effect is 0.786 meters and 0.852 meters without taking into account the smear zone effect. Meanwhile, the actual settlement that occurred in the field based on settlement plate (SP-01) was 0.867 meters and the magnitude of the preloading settlement without PVD was 0.512 meters. It can be concluded that the PVD combination preloading method is proven to accelerate consolidation time, while the improvement with the preloading method alone produces a relatively small decrease.